2013
DOI: 10.1152/jn.00459.2012
|View full text |Cite
|
Sign up to set email alerts
|

Short-term plasticity shapes activity pattern-dependent striato-pallidal synaptic transmission

Abstract: Kim J, Kita H. Short-term plasticity shapes activity pattern-dependent striato-pallidal synaptic transmission. J Neurophysiol 109: 932-939, 2013. First published November 28, 2012 doi:10.1152/jn.00459.2012.-The cortico-striato (Str)-globus pallidus external segment (GPe) projection plays major roles in the control of neuronal activity in the basal ganglia under both normal and pathological conditions. The present study used rat brain-slice preparations to address our hypothesis that the gain of this disynapti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
16
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 41 publications
(71 reference statements)
3
16
0
1
Order By: Relevance
“…33 But are these phenomena related? Evidence suggests that oscillations in some 34 certain bands in the striatum and the subthalamic nucleus (STN), the input structures 35 of the BG, are driven by cortical regions [22][23][24][25]. Taking this into account, in previous 36 work [26] we explored the impact of cortical rhythmic activity on the BG function and 37 we found that the former can completely shape which areas of the BG circuit are active.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…33 But are these phenomena related? Evidence suggests that oscillations in some 34 certain bands in the striatum and the subthalamic nucleus (STN), the input structures 35 of the BG, are driven by cortical regions [22][23][24][25]. Taking this into account, in previous 36 work [26] we explored the impact of cortical rhythmic activity on the BG function and 37 we found that the former can completely shape which areas of the BG circuit are active.…”
mentioning
confidence: 97%
“…In addition, 20 although both pathways are required for healthy action selection and were found to 21 contribute equally to the initiation of actions in [10], the indirect pathway is suppressed 22 during the execution of actions or action sequences [11], presumably because any 23 behavioural conflicts have already been resolved during movement [8]. 24 From another standpoint, low-frequency brain oscillations have been widely 25 implicated in both the function of the BG [12] and the process of decision 26 making [13][14][15][16][17]. Oscillations in the cortex mediate the processing of new 27 information [18], the dynamic formation of neural ensembles representing different 28 actions and the suppression of other task-irrelevant regions [19,20].…”
mentioning
confidence: 99%
“…Str-GPe synapses show very strong enhancement during repetitive activation, and thus the efficacy of the transmission is greatly dependent on the firing patterns of the Str neurons (Kim and Kita 2013). Str projection neurons fire with very different frequencies and patterns depending on the condition of the animal.…”
mentioning
confidence: 99%
“…To reveal how these diverse activity patterns of Str neurons alter the efficacy of the Str-GPe synapses, we characterized repetitive activation-induced short-term posttetanic enhancement (PTE) of Str-GPe synaptic inputs in rat brain slice preparations (Kim and Kita 2013). In that study, we focused on the development of PTE during single and repetitive conditioning stimuli (CS) and showed that the Str-GPe synapses have a very strong short-term PTE mechanism and that repetitive burst activation of the Str-GPe synapses, which mimic oscillatory burst firing of Str neurons, can sustain enhanced states of synaptic transmission for tens of seconds.…”
mentioning
confidence: 99%
See 1 more Smart Citation